Boats from a Silesian Coal Mine - Domżał, Robert (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In January and April 2013 two unique boats were discovered in the layer of silt in a 200-year-old Adit in the area of Zabrze (Silesia, southern Poland). They lay in a disused gallery about 22 m underground. The boats are similar in size: 5 m in length and less than a metre in width. Probably they were not used to transport the coal, but to carry the miners, tools and materials, possibly also for inspections of the mine site. It is presumably one of the oldest galleries carved out in coal in the world. Author discusses the circumstances of the discovery of the boats, their construction and their utility details.